The Necessity of Over-interpretation: Adorno, the Essay, and the Gesture of Aesthetic Experience - Anders Johansson (Estetika, 2013)
This article is a discussion of Theodor W. Adorno’s comment, in the beginning of ‘The Essay as Form’, that interpretations of essays are over-interpretations. I argue that this statement is programmatic, and should be understood in the light of Adorno’s essayistic ideal of configuration, his notion of truth, and his idea of the enigmatic character of art. In order to reveal how this over-interpreting appears in practice, I turn to Adorno’s essay on Kafka. According to Adorno, the reader of Kafka is caught in an aporia: Kafka’s work cannot be interpreted, yet every single sentence calls for interpretation. This paradox is related to the gestures and images in Kafka’s work: like Walter Benjamin, Adorno means that they contain sedimented, forgotten experiences. Instead of interpreting these images, Adorno visualizes the experiences indirectly by presenting images of his own. His own essay becomes gestural.